Climate-smart and nutrition-sensitive aquaculture in Odisha, India: a new horizon in sustainability, adaptation, and mitigation - Dubey, Sourabh Kumar; Panemangalore, Arun; Shenoy, Neetha; Gaikwad, Amar; Mohanty, Binimay; Baliarsingh, Bikram; Dutta, Sushil; Ratha, Baishnaba C.; Sethi, Binod; Pal, Moumita; Bhanja, Debananda; Acharya, Santanu (Edward Elgar Publishing, 2022)
The aquaculture sector plays very momentous role in providing nutritionally rich food and livelihood support to the impecunious communities across the developing world thus contributing directly and indirectly to their food security. However, the sector is vulnerable and impacted by climate variability. Changes in remote climate, rising temperatures, changing precipitation patterns, increased frequency of extreme weather events, sea-level rise, etc. are now limiting the production efficiencies and sustainability of the aquatic food production system. Odisha, on India's east coast, is one of the least developed states, with significant levels of food insecurity and malnutrition, particularly in rural areas. Droughts, floods, and other extreme weather phenomena are becoming more common and intense in Odisha. Amidst several restraints, Odisha offers luxuriant freshwater aquatic resources where aquaculture can potentially enhance resilience through improved resource use efficiencies and increased diversification of farmed species, locales of production, and management strategies. Against this backdrop, the government of Odisha has unveiled climate, nutrition, and gender-sensitive fisheries policies with "technological innovations" to address these complex interlinking issues of climate change and food security. The present communication portrayed some of the promising climate-smart, nutrition-sensitive food system approach which is expected to increase productivity, environmental sustainability, and climate change adaptability.